Corporate risk governance and board of directors: evidence from Malaysia listed companies / Lee Grace HweeLing and Angeline Kiew-Heong Yap. - Lee, Grace HweeLing; Kiew, Angeline Heong Yap (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
Corporate governance and risk management research continues to gain attention given the increasing cost of risk management and corporate governance failures which often remains underestimated attributed by the complex intertwining of risk management and corporate governance in such failures. In response, regulators had increased the significance of risk management activities and the board’s overall oversight responsibilities on risk governance. Prior studies provided conflicting outcomes on the relationship of corporate governance elements and board’s oversight effectiveness. This study aims to ascertain board attributes (board independence, board committee structure, board experience, corporate reporting and disclosure and dynamic and constructive dialogue adopted on risk governance matters) that contributes positively towards board’s oversight effectiveness on corporate risk governance. The findings based on top 100 Bursa Malaysia listed companies between 2011 to 2015 suggest that board committee structure, disclosure on risk management framework and detailed disclosure of risk management practices and processes are significantly positively related towards board’s oversight effectiveness on corporate risk governance. However, other elements such as board independence, board experience and dynamic and constructive dialogue on corporate risk governance do not contribute significantly. This study offers new insights on practices adopted by Malaysian listed companies on risk governance and help regulators to create greater awareness with respect to the intrinsic value derived from corporate risk governance practices and to formulate director’s training and development program to enhance effectiveness of board’s oversight on corporate risk governance.